Legalization of Isbat Nikah, Efforts to Enforce Law on Unregistered Marriages in Sosopan District, Padang Lawas Regency - Asmara (Getpress Management Journals, 2023)
This research focuses on the legalization process of isbat nikah as a means of enforcing the law on marriages conducted informally in Sosopan District, Padang Lawas Regency. The primary objective of this study is to identify and analyze the factors that necessitate the legalization of isbat nikah and its implications on the legal and social status of the citizens. The research methodology employed is qualitative, using a case study approach involving in-depth interviews, observations, and document analysis. The findings reveal that many marriages in Sosopan District are conducted without official registration, largely due to a lack of legal awareness and access to formal procedures. The legalization of marriage isbat is considered a crucial solution, providing legal and social protection for the couples and their children. The legal basis used in the isbat nikah process at the Sibuhuan Religious Court is the Compilation of Islamic Law, which allows the validation of marriages that do not have matrimonial impediments in accordance with Law No. 1 of 1974.